Réseau de parenté pendant le premier confinement : des liens intensifiés en temps d’incertitude ? - Veronika Kushtanina; Virginie Vinel (Temporalités)
This article examines the preservation of relationships with confined separately family members during the first wave of the pandemic, characterized as a time of uncertainty and disruption of daily temporalities. 4 300 responses were collected through an online questionnaire distributed during the spring of 2020. As face-to-face social relations were obstructed, we question how this separation of time and space has influenced the frequency of contacts. Has the pandemic strengthened or weakened ties with close and distant relatives? Did the disruption of daily rhythms affect contacts? The issue at stake is the continuity of caring for others, particularly the most fragile in an extended family, which is often little studied. Moreover, we analyze the gender and social class inequalities exacerbated by this period. As a whole, the frequency of contacts increased, especially with close family, but also – and this is the original discovery of this article – with more distant relatives. Paradoxically, activity during confinement had no effect on ties. In contrast, women and the “pivot generation” intensified their investment because of their central role in the kinship network. Persons with privileged backgrounds and those geographically distant from their family intensified long-distance relationships through digital tools, investing them as a temporality apart.